2014
DOI: 10.1007/s00221-013-3806-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic escitalopram treatment caused dissociative adaptation in serotonin (5-HT) 2C receptor antagonist-induced effects in REM sleep, wake and theta wave activity

Abstract: Several multi-target drugs used in treating psychiatric disorders, such as antidepressants (e.g. agomelatine, trazodone, nefazodone, amitriptyline, mirtazapine, mianserin, fluoxetine) or most atypical antipsychotics, have 5-hydroxytryptamine 2C (5-HT2C) receptor-blocking property. Adaptive changes in 5-HT2C receptor-mediated functions are suggested to contribute to therapeutic effects of selective serotonin reuptake inhibitor (SSRI) antidepressants after weeks of treatment, at least in part. Beyond the mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
1
Order By: Relevance
“…Kostyalik et al have described that SB-242084 elevated PW duration, and suppressed REMS which effect was attenuated by chronic ESC pretreatment, in rats. Regarding qEEG, they have found enhanced theta power during AW and also during REMS that was not further modified by chronic escitalopram pretreatment (Kostyalik et al, 2014). The thetaenhancing effect of the 5-HT 2C R-antagonist and thus the role of 5-HT 2C R in the regulation of theta activity have been supported by Hajos et al (2003b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kostyalik et al have described that SB-242084 elevated PW duration, and suppressed REMS which effect was attenuated by chronic ESC pretreatment, in rats. Regarding qEEG, they have found enhanced theta power during AW and also during REMS that was not further modified by chronic escitalopram pretreatment (Kostyalik et al, 2014). The thetaenhancing effect of the 5-HT 2C R-antagonist and thus the role of 5-HT 2C R in the regulation of theta activity have been supported by Hajos et al (2003b).…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, Kantor et al have demonstrated that although 0.3 and 1.0 mg/kg doses of the drug produced similar anxiolytic effects, only the higher dose affected the sleep-wake architecture prominently (wake-promoting effect with reduction of SWS-2), in Sprague-Dawley rats (Kantor et al, 2005). A REMS-reducing effect have been found at 1 mg/kg dose in Wistar rats, and theta power elevations during AW and REMS have also been observed following this treatment (Kostyalik et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…В контрольной группе они, возможно, носят ком-пенсаторный характер. В группах с постинсультной депрес-сией и апатией изменения в быстром частотном диапазоне ЭЭГ могут отражать дисбаланс в функционировании меди-аторных систем [20,21]. Через 12 мес также были получены противоположно направленные корреляции индекса бета 2-активности с по-казателями неврологического дефицита по шкале NIHSS в контрольной (отрицательные) и основной (положитель-ные) группах (см.…”
Section: з н а ч и м ы е р а з л и ч и я п а р а м е т р о в э э г у unclassified
“…Injections of ritanserin and ketanserin, possessing 5-HT 2A/2C receptor antagonist properties, induced a significant increase in SWS and a reduction of both REMS and wakefulness in rats [19–23]. However, our previous data show that SB-242084, a highly selective 5-HT 2C receptor antagonist, promotes wakefulness while decreases both deep slow wave sleep (SWS-2) and REMS [24, 25].…”
Section: Introductionmentioning
confidence: 99%